Agile Processes in Software Engineering and Extreme Programming 11th International Conference, XP 2010, Trondheim, Norway, June 1-4, 2010, Proceedings - Sillitti, Alberto.; Sillitti, Alberto.; Wang, Xiaofeng.; Wang, Xiaofeng.; Martin, Angela.; Martin, Angela.; Whitworth, Elizabeth.; Whitworth, Elizabeth. (Lecture Notes in Business Information Processing,, 2010)
Interest in agile development continues to grow: the number of practitioners adopting such methodologies is increasing as well as the number of researchers investigating the effectiveness of the different practices and proposing improvements. The XP c- ference series has actively participated in these processes and supported the evolution of Agile, promoting the conference as a place where practitioners and researchers meet to exchange ideas, experiences, and build connections. XP 2010 continued in the tradition of this conference series and provided an int- esting and varied program. As usual, we had a number of different kinds of activities in the conference program including: research papers, experience reports, tutorials, workshops, panels, lightning talks, and posters. These proceedings contain full - search papers, short research papers, and experience reports. Moreover, we have also included in these proceedings the abstracts of the posters, the position papers of the PhD symposium, and the abstract of the panel. This year we had two different program committees for evaluating research papers and experience reports. Each committee included experts in the specific area. This approach allowed us to better evaluate the quality of the papers and provide better suggestions to the authors to improve the quality of their contributions.